2011
DOI: 10.1002/eat.20898
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns of birth for subjects with bulimia nervosa, binge eating, and purging: Results from the National Women's Study

Abstract: In a national representative study of nontreatment seeking subjects significant differences in season of birth were found for subjects with lifetime histories of BN, binge eating and purging. © 2011 by Wiley Periodicals, Inc. (Int J Eat Disord 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This result is consistent with the findings of other authors . Only Brewerton et al were able to find significant differences across seasons between patients with and without BN. These differences could be an artifact because of the small sample size in the BN group ( n = 85).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the findings of other authors . Only Brewerton et al were able to find significant differences across seasons between patients with and without BN. These differences could be an artifact because of the small sample size in the BN group ( n = 85).…”
Section: Discussionsupporting
confidence: 93%
“…In a recent work, Brewerton, et al concluded that there were significant differences across seasons between patients with ( n = 85) and without ( n = 2898) BN among a nonclinical sample in the United States of America. Fall was the season with the highest relative number of births.…”
mentioning
confidence: 99%
“…Season of birth (SOB) has been shown to modify risk for several health outcomes, including a number of neuropsychiatric disorders (Brewerton, Dansky, O'Neil, & Kilpatrick, 2012;Cheng et al, 2013;Davies, Welham, Chant, Torrey, & McGrath, 2003;Disanto et al, 2012;Dome, Kapitany, Ignits, & Rihmer, 2010). In effect, there is evidence indicating that seasonality influences fetal growth and development (Currie & Schwandt, 2013;Flouris, Spiropoulos, Sakellariou, & Koutedakis, 2009;Strand, Barnett, & Tong, 2011;Watson & McDonald, 2007), which bears significance for psychiatric research.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: novelty seeking, 1 chess expertise, 2 smoking, 3 schizophrenia, 4,5 obesity, 6 and bulimia nervosa. 7 For females with AN, several studies report a season of birth bias with more births during the first 6 months of the year, 8 particularly in the spring months in Europe. 9,10 These findings are strengthened by a pooled meta-analyses of some of the UK samples 11 and a narrative review of the field.…”
Section: Introductionmentioning
confidence: 99%